2003
DOI: 10.1038/sj.leu.2402917
|View full text |Cite
|
Sign up to set email alerts
|

Successful peripheral blood stem cell mobilisation with filgrastim in patients with chronic myeloid leukaemia achieving complete cytogenetic response with imatinib, without increasing disease burden as measured by quantitative real-time PCR

Abstract: Imatinib mesylate (Glivec) is a selective inhibitor of bcr-abl tyrosine kinase, the product of the Philadelphia chromosome, which is the hallmark of chronic myeloid leukaemia (CML). With imatinib, complete cytogenetic response (CCR) can be achieved in over 70% of newly diagnosed patients with CML. However, the optimal long-term management of patients who achieve CCR after imatinib is unknown. With longer follow-up, it is anticipated that some patients are likely to progress and become candidates for autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…However, the enhanced reduction of imatinib mesylate -resistant quiescent cells resulting from intermittent exposure to G-CSF is additive with the imatinib mesylate effect and, thus, in combination, a greater overall reduction in CML cells is achieved. Notably, this outcome was obtained with an in vitro concentration of 20 ng/mL of G-CSF and 5 Amol/L imatinib mesylate, both of which are at the upper limit of those achieved with doses currently considered safe for use in CML patients (18,19,40). Improved kill of quiescent CD34 + CML cells exposed to imatinib mesylate in combination with high concentrations of a cocktail of growth factors has been recently reported by another group (41).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the enhanced reduction of imatinib mesylate -resistant quiescent cells resulting from intermittent exposure to G-CSF is additive with the imatinib mesylate effect and, thus, in combination, a greater overall reduction in CML cells is achieved. Notably, this outcome was obtained with an in vitro concentration of 20 ng/mL of G-CSF and 5 Amol/L imatinib mesylate, both of which are at the upper limit of those achieved with doses currently considered safe for use in CML patients (18,19,40). Improved kill of quiescent CD34 + CML cells exposed to imatinib mesylate in combination with high concentrations of a cocktail of growth factors has been recently reported by another group (41).…”
Section: Discussionmentioning
confidence: 84%
“…Previous in vitro studies of leukemic cells from patients with acute myeloid leukemia have shown that the susceptibility of these cells to killing by chemotherapeutic agents, especially cell cycle -specific agents such as cytarabine (14 -16), is enhanced by prior exposure to growth factors, such as granulocyte-colony stimulating factor (G-CSF), and that the acute myeloid leukemic cells are more sensitive in this regard than their normal counterparts (17). In addition, G-CSF has been safely and successfully used for peripheral blood stem cell mobilization in healthy donors and in CML patients treated with imatinib mesylate with no significant increase in BCR-ABL transcript levels by quantitative reverse transcription-PCR (18,19). G-CSF is currently being used in patients with CML to overcome imatinib mesylate -induced neutropenia as myelosuppression during imatinib mesylate therapy has been found to be associated with a poorer cytogenetic response (20,21).…”
mentioning
confidence: 99%
“…Yields were improved if the patients temporarily withheld imatinib for 3 weeks before collection. 96 Prior radiotherapy to significant amounts of red marrow is associated with mobilization failure, 97 probably because of combined direct HSC toxicity, niche toxicity, and toxicity to the niche-supporting cells. Radiotherapy may also increase the expression of protease inhibitors such as ␣1-antitrypsin that would diminish the protease storm during mobilization.…”
Section: How I Treat Poor Hsc Mobilizers 4533mentioning
confidence: 99%
“…tics (19 -22 ) and for transcriptional profiling (23,24 ). Some tests are already used in clinical practice, but before these methods can reach their full capacity, all technical steps, including sampling, RNA isolation, reverse transcription, cDNA quantification, and data analysis, must be carefully optimized and validated (25 ).…”
Section: Discussionmentioning
confidence: 99%